Economic Resilience Model of the Darul Istiqomah Islamic Boarding School in Manado in a Minority Community Through the Management of Productive Waqf - Hasan Jan, Radlyah; Nugraha, Amalia Kurnia; Anggrayni, Lilly; Hasan, Jamaludin (Management of Zakat and Waqf Journal (MAZAWA), 2026)
Islamic boarding schools frequently encounter financial vulnerabilities due to their reliance on sporadic donations, a condition often exacerbated by market limitations within Muslim-minority demographics. Although optimizing productive waqf assets offers a potential solution for institutional self-sufficiency, in reality, many governance practices remain consumptive and lack standardization. Addressing this issue, this study aims to analyze the strategies for empowering waqf land and their impact on economic independence at Pondok Pesantren Darul Istiqomah Manado. This research employs a descriptive qualitative method with a case study approach, operationalized through an in-depth investigation of a single managerial cycle at the research site using the POAC (Planning, Organizing, Actuating, and Controlling) framework. To ensure data validity and richness, informants were selected through purposive sampling based on their strategic authority and direct operational involvement, including the school leadership, the secretary, student representatives, and representatives from the Indonesian Waqf Board (BWI) of North Sulawesi. The results indicate that empowerment is implemented through asset diversification across three clusters: the boarding school complex for education and creative industries (bakery, laundry, and drinking water), the Loreng area for agriculture (corn and vegetables), and the Solog area as a Tahfiz center. This adaptive management significantly reduces monthly dormitory consumption costs by 20-25% and contributes 15-20% to the institution's annual budget. Despite successfully achieving initial financial independence as a survival strategy, the school's governance remains traditional (trust-based) and is not yet supported by written Standard Operating Procedures (SOPs). This study concludes that integrated waqf management is a strategic solution for the independence of educational institutions in minority areas, the implementation of which imperatively requires administrative system modernization to ensure long-term sustainability.